Flujo de venta del año 2019-2020 de la Empresa Inplanet S. A. sucursal Babahoyo. - Maliza Vera, Michael Omar (2022)
In this case study we will deal with the sales flows of the year 2019-2020 of the company inplanet.sa Babahoyo branch. Which is a company from Ecuador, its headquarters is in the city of Milagro whose management lies in providing internet service to the community. was incorporated on August 20, 2002 under the laws of the Republic of Ecuador, in the Milagro Canton, Guayas Province. In the financial aspects reflected in the years 2019-2020, the company In.Planet.S.A had sales of 4,218,198 dollars for the year 2019, while for the subsequent year 2020 they had sales of 5,172,088 dollars, which clearly represented an increase compared to the previous year. The case study that is carried out describes the sales flows, as well as showing us the income that it had for each activity carried out by the company, it also shows us the variations that there were from one year to another in the sales flows. The purpose of demonstrating this development is to analyze why there was a considerable variation in the sales of the year 2020 with respect to the previous year of 2019.